2016
DOI: 10.1021/jacs.6b10414
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis of Two-Dimensional 1T-TiSe2 with Charge Density Wave Transition by Chemical Vapor Transport

Abstract: Two-dimensional (2D) metallic transition metal dichalcogenides (TMDCs), such as 1T-TiSe, are ideal systems for exploring the fundamentals in condensed matter physics. However, controlled synthesis of these ultrathin materials has not been achieved. Here, we explored the synthesis of charge density wave (CDW)-bearing 2D TiSe with chemical vapor transport (CVT) by extending this bulk crystal growth approach to the surface growth of TiSe by introducing suitable growth substrates and dramatically slowing down the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 28 publications
3
74
0
2
Order By: Relevance
“…It should be mentioned that the formation of bulk TMD crystals is typically an endothermic process, and thus the sublimation temperature T 1 is mostly set higher than the deposition temperature T 2 . The CVT based methods are now regarded as one of the most reliable approaches to grow common bulk TMD crystals for both research and commercial purposes …”
Section: Cvt Based Synthesis Of 2d Transition Metal Dichalcogenidesmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be mentioned that the formation of bulk TMD crystals is typically an endothermic process, and thus the sublimation temperature T 1 is mostly set higher than the deposition temperature T 2 . The CVT based methods are now regarded as one of the most reliable approaches to grow common bulk TMD crystals for both research and commercial purposes …”
Section: Cvt Based Synthesis Of 2d Transition Metal Dichalcogenidesmentioning
confidence: 99%
“…From this point of view, source materials and the mineralizer can be regarded as the most decisive factors in the growth of TMD crystals. Thereafter, the reaction conditions could be optimized case by case, typically in an empirical way, and some representative reactions are summarized in Table 1 …”
Section: Cvt Based Synthesis Of 2d Transition Metal Dichalcogenidesmentioning
confidence: 99%
“…Bulk CDW materials such as 1T-VSe 2 [50], 1T-TaSe 2 [28], 2H-TaSe 2 [5,51] and 2H-NbSe 2 [52] have been reported by the CVT method in recent years. For synthesis of 2D CDW materials, recently, J. Wang et al reported controlled synthesis of two-dimensional 1T-TiSe 2 on sapphire substrates with sub-10-nm thickness [53] (Figure 5). It is essential to introduce a growth substrate to guide the 2D growth of TMDs and dramatically slow down the growth of the bulk counterpart in the CVT method.…”
Section: Chemical Vapor Transportmentioning
confidence: 99%
“…Although CVT is ubiquitously used to synthesize bulk crystals, it was only recently reported that atomically thin TMDs, including WS 2 , can be grown using CVT in a sealed ampule by carefully controlling mass transport . While using I 2 and metal chlorides as transport agents, the presented closed‐tube technique still requires metal oxides and sulfur as precursors, akin to CVD where stoichiometry is always a consideration.…”
mentioning
confidence: 99%